2011
DOI: 10.1007/s11664-011-1559-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cooling Rate on Thermoelectric Properties of n-Type Bi2(Se0.4Te0.6)3 Compounds

Abstract: A series of Bi 2 (Se 0.4 Te 0.6 ) 3 compounds were synthesized by a rapid route of melt spinning (MS) combined with a subsequent spark plasma sintering (SPS) process. Measurements of the Seebeck coefficient, electrical conductivity, and thermal conductivity were performed over the temperature range from 300 K to 520 K. The measurement results showed that the cooling rate of melt spinning had a significant impact on the transport properties of electrons and phonons, effectively enhancing the thermoelectric prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…[69][70][71]146] As ar esult, ar emarkably high zT of % 1.56 at 300 Kw as observed in p-type Bi 2Àx Sb x Te 3 nanograined alloys (Table 1). Recently,M Sw as used as one of the key processing technologiest of abricate nanograined TE alloys.…”
Section: Bottom-up Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…[69][70][71]146] As ar esult, ar emarkably high zT of % 1.56 at 300 Kw as observed in p-type Bi 2Àx Sb x Te 3 nanograined alloys (Table 1). Recently,M Sw as used as one of the key processing technologiest of abricate nanograined TE alloys.…”
Section: Bottom-up Methodsmentioning
confidence: 58%
“…This technique was proposed to prepare Bi 2 Te 3 -based ribbonsw ith ah igh density of nanograins. [69][70][71]146] As ar esult, ar emarkably high zT of % 1.56 at 300 Kw as observed in p-type Bi 2Àx Sb x Te 3 nanograined alloys (Table 1). It was reported that the formationof10-20 nm nanograins on the contact surface (ribbon and Cu wheel)o ft he melt-spun ribbon plays ac ritical role in the significant reduction of k lat .Aphotograph and the microstructure of our meltspun Bi 0.5 Sb 1.5 Te 3 ribbon are shown in Figure17.…”
Section: Top-down Methodsmentioning
confidence: 58%
“…In view of the successful implementation of the MS-SPS and BM-HP techniques in the p-type Bi 2 Te 3 (SE-MS-SPSed p-type (Bi,Sb) 2 Te 3 nanocomposites, section), it is instructive to implement the same nanostructuirng procedure in the n-type Bi 2 Te 3 . Interestingly, the ZT improvement of the n-type material turned out to be small [59,60,70,71,80,81]. We will discuss this discrepancy and possible solution in the section ''Why the MS-SPS procedure is less effective in n-type Bi 2 (SeTe) 3 nanocomposites''.…”
Section: Se-ms-spsed N-type Bi 2 (Sete) 3 Nanocompositementioning
confidence: 99%
“…A molten alloy thin stream is poured on a spinning wheel. [97][98][99] The melting heat is quickly transferred to the wheel followed by rotation, which sustains the amorphization of liquid continuously, producing thin tapes and ribbons. 100 The local cooling and cooling rate regulate the microstructure of the materials in the synthesis process and are maintained through processing parameters in melt spinning.…”
Section: Melt Spinning (Ms)mentioning
confidence: 99%